Village Plan Second Five Year Plan 1956-1961 Government of Saurashtra - Planning Commission (Planning Commission, 1956)
This is the fourth year of the Plan. The various developmental activities under the Plan are progressing satisfactorily and the results of progress are to a greater or lesser extent reflected in the increased economic activity in the country. We should now actively think about the formulation of the Second Five Year Plan.
Planning Department, Government of Saurashtra